The Secreted Lipoprotein, MPT83, of Mycobacterium tuberculosis Is Recognized during Human Tuberculosis and Stimulates Protective Immunity in Mice - Kao, Fan F. (Public Library of Science, 2012)
The long-term control of tuberculosis (TB) will require the development of more effective anti-TB vaccines, as the only licensed vaccine, Mycobacterium bovis bacille Calmette-Guérin (BCG), has limited protective efficacy against infectious pulmonary TB. Subunit vaccines have an improved safety profile over live, attenuated vaccines, such as BCG, and may be used in immuno-compromised individuals. MPT83 (Rv2873) is a secreted mycobacterial lipoprotein expressed on the surface of Mycobacterium tuberculosis. In this study, we examined whether recombinant MPT83 is recognized during human and murine M. tuberculosis infection. We assessed the immunogenicity and protective efficacy of MPT83 as a protein vaccine, with monophosphyl lipid A (MPLA) in dimethyl-dioctadecyl ammonium bromide (DDA) as adjuvant, or as a DNA vaccine in C57BL/6 mice and mapped the T cell epitopes with peptide scanning. We demonstrated that rMPT83 was recognised by strong proliferative and Interferon (IFN)-γ-secreting T cell responses in peripheral blood mononuclear cells (PBMC) from patients with active TB, but not from healthy, tuberculin skin test-negative control subjects. MPT83 also stimulated strong IFN-γ T cell responses during experimental murine M. tuberculosis infection. Immunization with either rMPT83 in MPLA/DDA or DNA-MPT83 stimulated antigen-specific T cell responses, and we identified MPT83(127–135) (PTNAAFDKL) as the dominant H-2(b)-restricted CD8(+) T cell epitope within MPT83. Further, immunization of C57BL/6 mice with rMPT83/MPLA/DDA or DNA-MPT83 stimulated significant levels of protection in the lungs and spleens against aerosol challenge with M. tuberculosis. Interestingly, immunization with rMPT83 in MPLA/DDA primed for stronger IFN-γ T cell responses to the whole protein following challenge, while DNA-MPT83 primed for stronger CD8(+) T cell responses to MPT83(127–135). Therefore MPT83 is a protective T cell antigen commonly recognized during human M. tuberculosis infection and should be considered for inclusion in future TB subunit vaccines.